Aktivitas Antijamur Fraksi Ekstrak Etanol Daun Pare (Momordica charantia L.) terhadap Microsporum canis ATCC 32699 - Reza Agung Sriwijaya; Rini Isromarina; Meyla Rosada (Jurnal Penelitian Sains, 2018)
Pare is one of the plants used as an herbal medicine, one of which is for infectious diseases. This study aimed to evaluate the antifungal activity ethanol extract fraction leaves of Pare. The extraction was carried out using maceration method and then fractionated using n-hexane, ethyl acetate and water solvents. The antifungal activity was determined using the agar diffusion method. The test fungus was using Microsporum canis at a serial concentration of 1,5%, 1% and 0,5%. The results of antifungal activity test of n-hexane fraction, ethyl acetate fraction and water fraction of Pare leaf ethanol extract showed the existence of inhibitory zone diameter. In the n-hexane fraction, ethyl acetate and water frac-tion the diameter of the largest inhibitory zone was 11,7 mm, 11,6 mm and 10,1 mm. Inhibitory zone showed that the fraction of ethanol extract of Pare leaves has antifungal activity.